The features of «productive» function of the state as economic subject - Khussainova, Zh.S.; Zhartay, Zh.; Semak, E.A.; Gordeyeva, Ye.A. (KSU Publ., 2018)
In article are considered features of «productive» function of the state as economic subject. Need and expediency of the state production of the net public benefits is most obvious. Not excludability is absolutely insuperable to them, and obviously there is no opportunity to replace expenses of the state coercion, if they are rather high, expenses on creation of a market mechanism of restriction of access to this benefit for «hare». When consumption is absolutely noncompetitive, price quotation of public goods or service in Pareto principle is inefficient as consumption of additional unit of the benefit brings benefit to the consumer without any expenses. Price quotation will reduce consumption, having caused under exploitation of the public benefits and a dead loss of usefulness. When the supply of net public goods through the market is possible, it won't provide achievement of the best (optimum) level of production. Result of research of authors is detection of features of «productive» function of the state on the example of the Republic of Kazakhstan, and also the problems which arose recently connected with the researched subject.
Экономикалық субъект ретінде мемлекеттің «өндірістік» функцияларының ерекшеліктері
Экономикалық субъект ретінде мемлекеттің «өндірістік» функцияларының ерекшеліктері
Keywords: «productive» function; public benefits; public benefits; social production; social aid; social security